2022
DOI: 10.3390/su14074242
|View full text |Cite
|
Sign up to set email alerts
|

Precision Ventilation in an Open-Plan Office: A New Application of Active Chilled Beam (ACB) with a JetCone Feature

Abstract: Mixing ventilation systems effectively improves thermal comfort in open-spaces due to adequate turbulent mixing of the cold stream with ambient air. This study introduces the concept of precision ventilation for achieving local thermal comfort in a mixing ventilation system. This precision ventilation system provides asymmetrical airflows from an active chilled beam (ACB) to each of the office occupants. These ACBs provide air velocities with different magnitudes and directions. To achieve different magnitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that a local air velocity range up to 1.2 m/s is considered acceptable by raising room temperatures up to 28 • C during experiments [43,45]. In the previous study on precision ventilation [30], single ACBs established high velocity zones by pushing more airflow towards the targeted zones. The airflow along the ceiling and walls reached the occupied zone for creating micro-climate zones in the dual desk-chair setup.…”
Section: Air Velocity Distributionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous studies have shown that a local air velocity range up to 1.2 m/s is considered acceptable by raising room temperatures up to 28 • C during experiments [43,45]. In the previous study on precision ventilation [30], single ACBs established high velocity zones by pushing more airflow towards the targeted zones. The airflow along the ceiling and walls reached the occupied zone for creating micro-climate zones in the dual desk-chair setup.…”
Section: Air Velocity Distributionmentioning
confidence: 95%
“…The grid independence test was carried out and tetrahedral meshes were generated in the entire computational domain with a 3.67 million element size (see Appendix A). The RNG k-ε turbulence model along with a similar setup (solver, boundary conditions, and numerical algorithm) was applied according to previous studies on precision ventilation [30,[34][35][36]. In simulations, the geometry of the ACBs was made circular in order to have radial flow and 50 L/s airflow (sum of primary and secondary airflows) produced from each ACB unit.…”
Section: Experimental and Simulation Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 12: ACBs with a JetCone feature showing asymmetrical airflow distribution (adapted from [214], [215])…”
Section: Acb With Jetconesmentioning
confidence: 99%